2009
DOI: 10.17221/43/2008-swr
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting regime on soil physical properties of wet thistle meadows

Abstract: Changes of selected soil physical properties (porosity P, soil organic matter SOM, bulk density ρ d , particle density ρ z , characteristics of water retention capacity -maximum capillary water capacity θ CMC , and non-capillary porosity P n ) of permanent grassland (wet, non-fertilized, thistle meadows ass. Angelico-Cirsietum palustris, crystalline complex area, Czech Republic) in the top soil layer (3-10 cm) managed under three regimes (uncut UC; cut once a year C1; cut twice a year C2) were monitored for on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The values of soil organic matter content belong to the main factors influencing bulk density (e.g., Duffková, Kvítek 2009;Ruehlmann, Körschens 2009;Tolimir et al 2020) and other physical soil properties (Huntington 2007); the decrease of soil organic matter content led to the higher values of bulk density (e.g., Sakin et al 2011). The values of bulk density also depend on the texture, mineral constituents and porosity (Baver et al 1972;Vopravil et al 2017b); correlations of bulk density with total porosity were reported by Hemmat et al (2010) etc.…”
Section: Resultsmentioning
confidence: 99%
“…The values of soil organic matter content belong to the main factors influencing bulk density (e.g., Duffková, Kvítek 2009;Ruehlmann, Körschens 2009;Tolimir et al 2020) and other physical soil properties (Huntington 2007); the decrease of soil organic matter content led to the higher values of bulk density (e.g., Sakin et al 2011). The values of bulk density also depend on the texture, mineral constituents and porosity (Baver et al 1972;Vopravil et al 2017b); correlations of bulk density with total porosity were reported by Hemmat et al (2010) etc.…”
Section: Resultsmentioning
confidence: 99%
“…The disturbed and undisturbed (using a Kopecky cylinder core) soil samples (3 samples per each of the studied soil depths on the DM as well as the UM) for the determination of the selected physical properties (particle and bulk density, total porosity, maximum capillary water capacity, minimum air capacity, water retention capacity and saturated water content) were taken on July 11, 2018. These properties are described in the works by Flint and Flint (2002a, b) and Duffková and Kvítek (2009). The maximum capillary water capacity was obtained after 2 h suction (on filter paper) of the fully saturated soil samples.…”
Section: Methodsmentioning
confidence: 90%
“…These differences may be due to the mentioned tile drainage; the management methods may also influence these soil properties. For example, Duffková and Kvítek (2009) reported that some chemical and physical soil properties (soil organic carbon, particle and bulk density, porosity, maximum capillary water capacity, etc.) of the studied drained and undrained permanent grasslands were significantly influenced by the used management methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation